2011
DOI: 10.1007/s00011-011-0310-0
|View full text |Cite
|
Sign up to set email alerts
|

Human thymic stromal lymphopoietin enhances expression of CD80 in human CD14+ monocytes/macrophages

Abstract: TSLP induces CD80 expression in human peripheral blood CD14(+) monocytes/macrophages; this indicates monocyte/macrophage activation. This may be associated with their differentiation into myeloid dendritic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…The degree of mCD14 down-modulation on monocytes suggests the preferential expansion of a small CD14 low subset and not a globally altered transcription/translation rate. This, for example, is in line with the increased percentage of CD14 −/low monocytes upon in vitro culture in the presence of TSLP, an important cytokine in allergic asthma 40 . Monocytes are heterogeneous, with major (CD14 high ) and minor (CD14 low ) subsets 32 .…”
Section: Discussionsupporting
confidence: 73%
“…The degree of mCD14 down-modulation on monocytes suggests the preferential expansion of a small CD14 low subset and not a globally altered transcription/translation rate. This, for example, is in line with the increased percentage of CD14 −/low monocytes upon in vitro culture in the presence of TSLP, an important cytokine in allergic asthma 40 . Monocytes are heterogeneous, with major (CD14 high ) and minor (CD14 low ) subsets 32 .…”
Section: Discussionsupporting
confidence: 73%
“…In addition, TSLP can enhance eosinophil survival, up-regulate surface expression of adhesion molecules and induce the release of inflammatory cytokines and chemokines from human eosinophils [ 47 ]. Finally, TSLP amplifies M2 macrophage polarization [ 48 , 49 ]. Since eosinophils and, at a lower extent, basophils/mast cells are important components of the HL lymph node infiltrate, it is conceivable that IL-31 and/or TSLP contribute to the recruitment, survival and activation of these cell types and, more in general, polarize immune responses towards a tumor promoting functional state.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cells, which highly express TSLP in allergic Th2‐based disorders, such as atopic dermatitis and asthma (18), were originally identified as the principal source of TSLP. More recently, several studies have shown that TSLP can be expressed by other cell types, including fibroblasts, mast cells, CD68+ macrophages (19, 20), and dendritic cells (21). In our study, we observed strong expression of TSLP in the skin of dcSSc patients mainly in immune cells, colocalizing with CD163+ cells, a marker for resident activated macrophages (22), and also colocalizing with a few CD4+ and CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%